39.2k views
4 votes
Find the inverse function of f(x) = x+2/x+1

User Hannele
by
6.1k points

2 Answers

3 votes

Answer:


f^(-1)(x) =
(2-x)/(x-1)

Explanation:

Let y = f(x) and rearrange making x the subject

y =
(x+2)/(x+1) ( multiply both sides by (x + 1)

y(x + 1) = x + 2 ← distribute left side

yx + y = x + 2 ( subtract x from both sides )

yx - x + y = 2 ( subtract y from both sides )

yx - x = 2 - y ← factor out x on the left side

x(y - 1) = 2 - y ← divide both sides by (y - 1 )

x =
(2-y)/(y-1)

Change y back into terms of x, thus


f^(-1)(x) =
(2-x)/(x-1)

User Zeograd
by
5.4k points
4 votes

Answer:
\bold{f^(-1)(x)=(2-x)/(x-1)\qquad \implies \qquad f^(-1)(x)=-(x-2)/(x-1)}

Explanation:

Inverse is when you swap the x's and y's and solve for y. f(x) is y.


y=(x+2)/(x+1)\\\\\\\\\underline{\text{Swap the x's and y's}}\\\\x=(y+2)/(y+1)\\\\\\\\\underline{\text{solve for y}}\\\\x(y+1)=y+2\\\\xy+x=y+2\qquad \qquad \text{distributed x into y+1}\\\\xy-y=2-x\qquad \qquad \text{subtracted x and y from both sides}\\\\y(x-1)=2-x\qquad \qquad \text{factored out y on the left side}\\\\\\y=(2-x)/(x-1)}\qquad \qquad \text{divided both sides by x-1}


\large\boxed{f^(-1)(x)=(2-x)/(x-1)}

This is equal to:
f^(-1)(x)=-(x-2)/(x-1)

User Bjhuffine
by
5.5k points